Edukasi Krim Berbahaya Mengandung Merkuri & Cara Cek BPOM pada Siswa Siswi SMAN 1 Alalak - Yulianita Pratiwi Indah Lestari; Dina Azizah; Dhea Indah Cahyani; Dita Putri Aulia (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Excessive attention to aesthetic skin problems, the widespread use of cosmetics by the public with all the positive and negative impacts received by the skin, have also brought developments in medical science in general, in the field of Dermatology in particular. The purpose of carrying out community service activities in the form of counseling about "Education on dangerous creams containing mercury & how to check BPOM" is to educate and provide information about dangerous creams containing mercury and how to check BPOM on beauty products used to pay attention to the use of cosmetics, especially creams on the face and how to respond to the circulation of cosmetics with dangerous chemicals. Community Service activities in the context of counseling, information and education for high school students regarding safe and dangerous cosmetics have been well implemented. Initially, in the pretest, only 5 of 5 questions were correct with 19 students out of a total of 33 students, then in the posttest, they answered 5 out of 5 questions correctly with 21 students out of a total of 28 students. This means experiencing success in increasing knowledge after holding educational activities.